Genital human papillomavirus infection in the male sexual partners of women with isolated vulvar lesions. Issue 2 (1st March 2006) - Taner, M. Z.; Taskiran, C.; Onan, M. A.; Uluturk, A.; Himmetoglu, O.
Abstract : The purpose of this study was to detect human papillomavirus (HPV) positivity in the male sexual partners of women with isolated vulvar lesions. The male counterparts of the females were subjected to detailed physical and peniscopic evaluations. After the gross inspection, 5% acetic acid was applied and the whole genital organs were evaluated using a colposcope. Overall, 47 male sexual partners with isolated vulvar HPV lesions were included. None of the patients had condylomata acuminata. Twenty-six patients (55%) had papular or papillary lesions, and 21 (45%) had flat acetowhite lesions. Biopsies were taken from all these suspicious areas for histopathologic examination. Overall, 41 patients (87%) had the exact characteristics of HPV on biopsy specimens. Ninety-two percent of patients (24/26) having papular and/or papillary lesions on peniscopy had HPV on biopsy, while 81% of patients (17/21) who had acetowhite flat lesions had biopsy-confirmed HPV lesions. In conclusion, it is important to assess the male sexual partners of women with HPV-related lower genital tract disease. Peniscopy is valuable for detecting lesions, and histopathologic confirmation is mandatory.